Traditional Chinese Medicine holographic scraping combined with moxibustion in the treatment of targeted therapy and immunotherapy-associated diarrhea in a patient with renal cell carcinoma (中医全息刮痧联合艾灸治疗1例肾恶性肿瘤患者靶向治疗和免疫治疗相关腹泻的护理体会) - JI Yunfei (吉云飞); LI Xu (李旭); SONG Libo (宋丽波); LI Mingzhu (李明珠); SONG Henan (宋鹤楠); ZHANG Miao (张淼) (中西医结合护理)
This paper reviewed the effect of Traditional Chinese Medicine holographic scraping combined with moxibustion therapy on a patient with renal malignant tumor who had diarrhea adverse reaction of targeted therapy and immunotherapy, and summarized the relevant nursing experience. By TCM syndrome differentiation holographic scraping combined with moxibustion treatment were carried out. Comprehensive nursing measures including life guidance, diet guidance, psychological guidance and other interventions were carried out during the treatment. The diarrhea symptom of the patient was effectively improved. (本文总结1例肾恶性肿瘤患者靶向治疗和免疫治疗出现腹泻不良反应采用中医全息刮痧联合艾灸治疗的护理体会。基于中医辨证, 采取全息刮痧联合艾灸治疗, 配合生活指导、饮食指导、心理指导等综合干预, 有效改善患者腹泻症状, 提高生活质量。)